The influence of professional qualification on customer perceptions of accounting services quality and retention decisions - Zaman Groff, Maja; Slapničar, Sergeja; Štumberger, Neža (Journal of Business Economics and Management, 2015)
The purpose of this paper is to examine whether professional qualification in- creases the quality of accounting services as perceived by the customers. We advance the measurement of service quality by industry-specific indicators and establish four dimen- sions of accounting service quality. We analyse the impact of professional qualification on these dimensions of quality and the impact of these dimensions on customers’ retention decisions. The analysis is based on survey data of 237 Slovenian small and micro firms that outsource accounting. We find that professional qualification is positively associated with only one of the perceived service quality dimensions – accounting competences – and only assurance, responsiveness and reliability and empathy are positively associated with customers’ retention decisions. Limitations of the study are attributed to the measure- ment of service quality as perceived by the customers. However, this is the only factor of choice that ultimately counts in the competitive market for accounting services. First published online: 02 Sep 2014